One-Year Review Of Reduced Fetal Movements In Izzat Ali Shah MCH Center: A Predictor Of Poor Perinatal Outcome - Humera Rani; Gulwish Salahuddin; Ayesha Naz; Noreen Majeed; Faiza Safdar; Shazia Rafique (Journal of Rawalpindi Medical College)
Objectives: To find out common causes of reduced fetal movements. The purpose is to reduce perinatal morbidity and mortality.